2014
DOI: 10.1063/1.4895967
|View full text |Cite
|
Sign up to set email alerts
|

Covalent dependence of octahedral rotations in orthorhombic perovskite oxides

Abstract: The compositional dependence of metal-oxygen BO6 octahedral distortions, including bond elongations and rotations, is frequently discussed in the ABO3 perovskite literature; structural distortions alleviate internal stresses driven by under- or over-coordinated bond environments. Here we identify the dependence of octahedral rotations from changes in metal-oxygen bond covalency in orthorhombic perovskites. Using density functional theory we formulate a covalency metric, which captures both the real and k-space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 57 publications
3
52
1
Order By: Relevance
“…Previous studies have shown that Nb doping enhances T S of STO to higher temperatures due to the local changes in the hybridization between the (Ti, Nb)-d orbitals and O-2p orbitals [36]. Another important factor is the covalency of the transition metal-oxygen bond [37,38]. Ab initio calculations have shown that the octahedral tilting angle in KMF 3 (M = transition metal) decreases linearly with the electron occupancy of the π-bonding t 2g orbitals of the transition metal.…”
Section: +mentioning
confidence: 99%
“…Previous studies have shown that Nb doping enhances T S of STO to higher temperatures due to the local changes in the hybridization between the (Ti, Nb)-d orbitals and O-2p orbitals [36]. Another important factor is the covalency of the transition metal-oxygen bond [37,38]. Ab initio calculations have shown that the octahedral tilting angle in KMF 3 (M = transition metal) decreases linearly with the electron occupancy of the π-bonding t 2g orbitals of the transition metal.…”
Section: +mentioning
confidence: 99%
“…We understand this be- havior as follows: the magnetic moment only depends on the Mn atoms, and any small changes to it are induced by inductive effects from the A cations that weakly change the length and covalency of the Mn-O bond. 60 The electronic density of states (not shown) also primarily consists of O 2p-states at the top of the valence band and W 5d-states at the bottom of the conduction band. The A and A cations contribute states far from these band edges, and as a result their chemistry does not significantly impact the band gap.…”
Section: Ground State Structuresmentioning
confidence: 99%
“…This is because these modes mainly correspond to octahedra rotations, which are largely insensitive to the on-site electron localization at metal center. 44 On the other hand, electron correlation localizes the electron in the t 2g orbitals, reducing the Ti-O bond length, and can harden those IR modes that directly alter the Ti-O bond length [ Fig. 7(b)].…”
Section: B Electron Correlation Effectsmentioning
confidence: 99%